Influence of type of muscle contraction and gender on postactivation potentiation of upper and lower limb explosive performance in elite fencers - Tsolakis, C.; Bogdanis, G.C.; Nikolaou, A.; Zacharogiannis, E. (Journal of Sports Science and Medicine, 2011)
The purpose of this study was to evaluate the postactivation potentiation (PAP) effect of isometric and plyometric contractions on explosive performance of the upper and the lower limbs in male and female elite athletes. Thirteen male and ten female international level fencers performed four protocols of either isometric (3 sets of 3 sec) or plyometric (3 sets of 5 repetitions) bench and leg press, in a within subject randomized design. Before and immediately after the PAP treatment and following 4, 8, 12 min, explosive performance was measured by performing a countermovement jump (CMJ) or a bench press throw. Statistical analysis revealed significant time effect for peak leg power during the CMJ (p < 0.001) only for men, with values after the isometric PAP treatment being lower than baseline at the 8 and 12 min time points (by 7.5% (CI95% = 3.9-11.2%) and 8.7% (CI95% = 6.0-11.5%, respectively), while after the plyometric PAP treatment peak leg power remained unchanged. A significant negative correlation was found between leg strength (as expressed by 1-RM leg press performance) and the change in peak leg power between baseline and after 12 min of recovery only in male fencers (r = -0.55, p < 0.05), suggesting that stronger individuals may show a greater decrease in peak leg power. Based on the above results we conclude that lower body power performance in international level fencers may be negatively affected after isometric contractions and thus they should be advised against using isometric exercises to induce PAP with the protocol prescribed in the present study. Furthermore, gender and strength level must be considered in the practical application of PAP. © Journal of Sports Science and Medicine.